Cultural knowledge as opportunities for empowerment: Learning and development for Mexican Indigenous youth. Issue 3 (3rd July 2021) - Casanova, Saskias; Mesinas, Melissa; Martinez-Ortega, Sarait
ABSTRACT: Educators are often unaware of assets Mexican Indigenous children possess that originate from their cultural practices. Using Critical Latinx Indigeneities and Indigenous Heritage Saberes, our studies focus on three unique Indigenous learning communities that provide opportunities of empowerment for these students. We examine the experiences of Triqui middle school students in a Youth Participatory Action Research club and how it facilitated their use of research as a decolonizing tool to hold knowledge inside the school. We explore how Oaxacan students maintain their cultural traditions via a learning community created byan Oaxacan philharmonic band. Lastly, we investigate the experiences of Yucatec-Maya youth with cultural community organization programs that instill knowledge of and pride in their Indigenous identity. Our studies contribute to the critical conversations about equity in education for Mexican Indigenous youth. Recommendations are made for educators and community organizations working with Mexican Indigenous students.